Impaired bolus clearance in asymptomatic older adults during high‐resolution impedance manometry. Issue 12 (26th June 2016) - Cock, C.; Besanko, L.; Kritas, S.; Burgstad, C. M.; Thompson, A.; Heddle, R.; Fraser, R. J. L.; Omari, T. I.
Abstract: Background: Dysphagia becomes more common in old age. We performed high‐resolution impedance manometry (HRIM) in asymptomatic healthy adults (including an older cohort >80 years) to assess HRIM findings in relation to bolus clearance. Methods: Esophageal HRIM was performed in a sitting posture in 45 healthy volunteers ( n  = 30 young control, mean age 37 ± 11 years and n  = 15 older subjects aged 85 ± 4 years) using a 3.2‐mm solid‐state catheter (Solar GI system; MMS, Enschede, The Netherlands) with 25 pressure (1‐cm spacing) and 12 impedance segments (2‐cm intervals). Five swallows each of 5‐ and 10‐mL liquid and viscous bolus were performed and analyzed using esophageal pressure topography metrics and Chicago classification criteria as well as pressure‐flow parameters. Bolus transit was determined using standard impedance criteria. A p ‐value <0.05 was considered significant. Key Results: Impaired bolus clearance occurred more frequently in asymptomatic older subjects compared with young controls (YC) during liquid (40 vs 18%, χ 2  = 4.935; p  < 0.05) and viscous (60 vs 17%; χ 2  = 39.08; p  < 0.001) swallowing. Longer peristaltic breaks ( p  < 0.05) and more rapid peristalsis (L: p  < 0.004, V: p  = 0.003) occurred in the older cohort, with reduced impedance‐based clearance for both bolus consistencies (L: p  < 0.05, V: p  < 0.001). Decreased peristaltic vigor (distal contractile integral <450 mmHg/s/cm) was associated with reduced liquid clearance in both age groups ( p  < 0.001) and of viscous swallows in the older group ( p  < 0.001). Impedance ratio, a marker of bolus retention, was increased in older subjects during liquid ( p  = 0.002) and viscous ( p  < 0.001) swallowing. Conclusions & Inferences: Impaired liquid and viscous bolus clearance, esophageal pressure topography, and pressure‐flow changes were seen in asymptomatic older subjects. Abstract : This study performed esophageal HRIM in 45 volunteers to assess the effects of age on Chicago Classification and esophageal pressure‐flow parameters. Impaired bolus clearance occurred more frequently in older subjects, with larger peristaltic breaks, more rapid contractions, and reduced LES relaxation. These data will assist interpretation of clinical HRM studies in older dysphagic patients.